Management Information of Public Institutions: Implementation of Information Management in Public Institutions - Annisa Fajriyah; Rayhan Musa Novian (Record and Library Journal, 2023)
Background of the study: Information management in an organization or institution, especially for institutions related to public information needs, has an important role. Purpose: This study provides an overview and view of how the information management process is carried out in several public institutions, how it is currently developing, and what factors affect the implementation of information management in each public institution. Method: The method used in compiling this paper is a qualitative descriptive research. Using an interview and literature study with several literatures related to the information management framework implemented in several countries and institutions that the author has carried out himself. Findings: The results of this study provide an understanding of the situation and conditions in each institution in managing its information, so that it can be a view for other institutions in designing and managing information in their own environment. Conclusion: The implementation of information management that occurs in every public body is directly or indirectly influenced by the birth of the Public Information